Synthesis of Nanosized Ag0.9Li0.1(Nb0.7Ta0.3)O3 Ceramic Powder and Investigation on its Property - Yan, Yuqing; Wen, Yugang (Asian Journal of Chemistry, 2012)
In this communication, Ag0.9Li0.1(Nb0.7Ta0.3)O3 (ALNT) mixed oxide powder was synthesized by citrate wet chemical method. TG-DTA, XRD and TEM analyses showed that the reaction temperature was 800 ºC, the calcining time was 3 h and the product was pure Ag0.9Li0.1(Nb0.7Ta0.3)O3 in well-dispersed grain structure (35 nm in average). The dielectric constant of ceramic sample prepared under traditional techniques is 516, dielectric loss tgd is 4.7 × 10-4.